Implementing the Capital Asset Pricing Model in Forecasting Stock Returns: A Literature Review - Juniawan Mandala; Josua Panatap Soehaditama; Moch Arif Hernawan; Ika Utami Yulihapsari; Maya Sova (Indonesian Journal of Business Analytics, 2023)
dfyfrdf